Analiza porównawcza efektywności powszechnych towarzystw emerytalnych na przykładach firm z grup kapitałowych Warta i PKO BP - Poteraj, Jarosław (Comparative Analysis of the Public Pension Societies on the Example of Companies From Warta and PKO Groups, 2009)
On the basis of the public pension societies from WARTA and PKO capital groups the author makes the efficiency analysis in two scientific perspectives - of the company and the owners of capital. Research methods used by the author were ROE indicator method and NPV method, enriched by IRR method. In the summary, the author concludes that the PKO project reveals the high efficiency in the case of ROE indicator at the level over 20%, and negative in the long-term owners perspective, measured by IRR, the level was -1.32%. The WARTA project in the last years reveals positive values of ROE indicator, but in 2008 lower than PKO project, and should be negatively assessed in the long-term owners perspective: the IRR level was -14.89%
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 252-261